Problems of the Growing Personality Formation in the New Historical Stage of Scociety Development - D. I. Feldshtein (Obrazovanie i Nauka)
The paper, based on the author’s report at the General Assembly of the State Academy of Sciences and Russian Academy of Education on 29 October 2013, raises the urgent problems of childhood and children’seducation, and outlines the main research trends of the Russian Academy of Education: identification of the social environment and specificities of personal growth, exploration of new principles, ways, conditions, opportunities and prospects of educational system renovation. In the era of uncertainty and transformed consciousness, the world perception and behavior psychology of the growing generation require the radical renewal of format and content of education and upbringing. The research demonstrates that the young generation, endowed with the new opportunities and abilities, considerably outstrips the previous generations. However, the children’s cognitive development, energy and active behavior are declining, and the emotional discomfort is rising. Many children are unwilling to learn as education can no longer provide the positive socialization. There is a large group of children with unfavorable, problematic psychic development in ontogenesis, as well as a number of contradictive psycho physiological phenomena that require extensive research and development of a fundamentally new educational concept.